2009
DOI: 10.1186/1476-069x-8-39
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in the population exposed to dioxin after the "Seveso accident": twenty years of follow-up

Abstract: BackgroundThe Seveso, Italy accident in 1976 caused the contamination of a large population by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Possible long-term effects have been examined through mortality and cancer incidence studies. We have updated the cancer incidence study which now covers the period 1977-96.MethodsThe study population includes subjects resident at the time of the accident in three contaminated zones with decreasing TCDD soil levels (zone A, very high; zone B, high; zone R, low) and in a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
4
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 37 publications
6
101
4
3
Order By: Relevance
“…However, very high doses may, in addition, cause cancer indirectly; one of the proposed mechanisms is oxidative stress and the subsequent oxygen damage to DNA [72]. TCDD has also been shown to exert an antiestrogenic activity in the presence of estrogens, and estrogenic property in the absence of estrogen [73].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very high doses may, in addition, cause cancer indirectly; one of the proposed mechanisms is oxidative stress and the subsequent oxygen damage to DNA [72]. TCDD has also been shown to exert an antiestrogenic activity in the presence of estrogens, and estrogenic property in the absence of estrogen [73].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…In the immediate aftermath, typical effects of exposure to polychlorinated hydrocarbons such as chloracne were observed mainly in children [74], an excess risk of lymphatic and hematopoietic tissue neoplasms in the most exposed zones was reported [73].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…Breast cancer among females was found to be below expectations in the most contaminated zones [63] and a 15-year mortality study after the ''Seveso accident'' showed no increase for breast cancer among females exposed to TCDD in comparison with the population of a surrounding non contaminated area [64]. On the other hand, Pesatori et al [65] mentioned an increased risk of breast cancer of females in the most contaminated zone 15 years since the accident (five cases, risk ratio 2.57; 95% CI, 1.07-6.20). Dioxin levels in the archived area that were collected soon after the explosion showed that the hazard ratio for breast cancer associated with the 10-fold increase of TCDD levels in serum was significantly increased to 2.1 (95% confidence interval, 1.0-4.6) [66].…”
Section: Dioxinsmentioning
confidence: 99%
“…These very same VPF figures could also be used to estimate the monetized benefits of regulations that reduce the risk of industrial accidents where carcinogens are released into the environment (Pesatori et al, 2009) or that impose higher emission standards on hazardous or solid waste incinerators (Zambon et al, 2007).…”
Section: Benefits In the Naples And Caserta Provincesmentioning
confidence: 99%